2015
DOI: 10.1182/blood.v126.23.5081.5081
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Maintenance Therapy Is an Effective Therapy in over-Sixties with Mantle Cell Lymphoma

Abstract: Introduction Mantle cell lymphoma (MCL) is a rare B-cell non-Hodgkin lymphoma (NHL) accounting for 5 percent of NHLs. Most patients with MCL are 60 years of age and older. The prognosis of patients with MCL is moderately aggressive and variable; the median overall survival is 3-5years. MCL international prognostic index(MIPI)is related to prognosis of the patients with MCL, however, it is unclear whether MIPI predicts outcomes of MCL over sixties. Out therapeutic strategy in elderly patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In young newly diagnosed patients, treatment often takes the form of high dose chemotherapy in combination with rituximab, followed by autologous stem cell transplant (ASCT). In older patients, rituximab has demonstrated efficacy as maintenance therapy after induction chemotherapy (often CHOP or CVP) [ 46 ]. Results from a recent international phase III trial indicate that rituximab maintenance may be useful in young patients after ASCT as well, with 4-year overall survival of 78% [ 47 ].…”
Section: Related Targets In the Treatment Of Mantle Cell Lymphomamentioning
confidence: 99%
“…In young newly diagnosed patients, treatment often takes the form of high dose chemotherapy in combination with rituximab, followed by autologous stem cell transplant (ASCT). In older patients, rituximab has demonstrated efficacy as maintenance therapy after induction chemotherapy (often CHOP or CVP) [ 46 ]. Results from a recent international phase III trial indicate that rituximab maintenance may be useful in young patients after ASCT as well, with 4-year overall survival of 78% [ 47 ].…”
Section: Related Targets In the Treatment Of Mantle Cell Lymphomamentioning
confidence: 99%
“…Diffuse large B-cell lymphoma is the most common type of NHL, representing 30–40% of all lymphoma diagnoses in Western countries ( 17 , 18 ). Since the World Health Organization’s (WHO’s) consensus in 2008, DLBCL has been categorized as germinal center B-cell-like (GCB), activated B-cell-like (ABC), or as unclassifiable lesions which do not fit either profile ( 19 ).…”
Section: Clinical Impact Of Rituximab In B-cell Nhl Treatmentmentioning
confidence: 99%
“…The first phase II single-arm trial for treating DLBCL with rituximab was reported in 2001, studying patients who had aggressive, untreated NHL. Thirty-three patients were included in this trial; the majority of patients (67%) had DLBCL ( 17 ). The study showed a 94% overall response rate (ORR) compared with historical CHOP controls (80–90%) and 61% CR compared with historical CHOP controls (44–55%), with only two patients experiencing disease progression by week 24 ( 21 ).…”
Section: Clinical Impact Of Rituximab In B-cell Nhl Treatmentmentioning
confidence: 99%
See 2 more Smart Citations